(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
One of the main goals of teaching mathematics is to prepare students for everyday life, as well as to develop their personality through mathematics. Mathematics makes it possible to ensure the formation of both subject and general educational (meta-subject) skills of schoolchildren. All key competencies can be implemented in mathematics lessons. Knowledge, skills and competencies in mathematics lessons must be formed through special assignments and tasks.